Development of delay tolerant network with automatic ad-hoc mode - Azman, Muhammad Affandy (2016)
Delay Tolerant Network (DTN) is known as a solution to an Internet network where connectivity is an issue. Bytewalla is an existing application which uses smartphone as a physical transport of data between these intermittent networks. However, the application depends solely on infrastructure to establish network connectivity. Because of this, data packets will only be transferred to users and servers through an access point which limits the ability to multi hop instantaneously to nearby user resulting in less reliable data transfer. To overcome this problem, Bytewalla needs a mechanism which enables each user to connect to each other to send and forward data automatically without using an access point. An automated mechanism is proposed for ad hoc connectivity between smart-phones to ensure connectivity with high successful transfer rate. This thesis presents an automated mechanism called Delay Tolerant Network with Automatic Ad hoc (DTN-AAH). In comparison to Bytewalla, DTN-AAH shows shorter delay since nodes are able to cross-connect to other platform (infrastructure/ad hoc) that improves reliability. This thesis also presents simulation studies on DTN-AAH to investigate the performance of the system. A DTN-AAH Network Management Tool was created to ease users to perform DTN related functions such as sending and reading messages without hassle by creating a user-friendly web-based interface.